Dolabellane diterpenes from the Caribbean soft corals Eunicea laciniata and Eunicea asperula and determination of their anti HSV-1 activity (2017)
=olabellane diterpenes have considerable antiviral activityy but most studies have been focused towards compounds isolated from Dictyota brown algaeT %lthough soft corals are also a significant source of these diterpenesy their antiviral potential has not been studied in detailT With the aim of assessing the biological activity of marine sourcesy we evaluated the dolabellane content in the soft corals Eunicea laciniata and E. asperula collected in Santa Martay μolombian μaribbeanT =olabellanes 657 were isolated from E. laciniata while compounds Ky : and 0 were isolated from E. asperulaT %ll compounds were identified by NMRy éμA9OMSy optical rotation and comparison with previously reported dolabellanesT éμA9OMS analyses showed that dolabellatrienone JKz transforms into compounds : and 0 as oxidation products upon prolonged storage) howevery those compounds were also naturally present in the extract of the studied organismsT Pure dolabellanes were tested in vitro in antiviral assays against qSVA5T μompound 7 inhibited virus replication in infected cells JW:TWI of inhibition at f4 μMz without cytotoxic effect Jμμf4 ; EfEzy showing similar activity to the positive control %cyclovir®T Thusy compound 7 is an interesting candidate for further studies of dolabellanes as antiviralsT